2020
DOI: 10.1002/jlb.3ma0520-054r
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophils activated by TLR8 agonists, with or without IFNγ, synthesize and release EBI3, but not IL-12, IL-27, IL-35, or IL-39

Abstract: The IL-12 family of cytokines plays crucial functions in innate and adaptive immunity. These cytokines include heterodimers sharing distinct (IL-12A, IL-23A, and IL-27A) with two (IL-12B and Epstein-Barr virus induced gene 3 [EBI3]) chains, respectively, IL-12 (IL-12B plus IL-12A) and IL-23 (IL-12B plus IL-23A) sharing IL-12B, IL-27 (EBI3 plus IL-27A), IL-35 (EBI3 plus IL-12A), and IL-39 (EBI3 plus IL-23A) sharing EBI3. In this context, we have recently reported that highly pure neutrophils incubated with TLR8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(175 reference statements)
1
11
0
Order By: Relevance
“…To date, TLR8 ligands, have been shown to trigger or modulate a variety of effector functions of neutrophils, including the survival, the respiratory burst, the phagocytic activities, and the formation of NETs (Thomas and Schroder, 2013). In our research, TLR8 agonists, including R848 and other compounds, such as CL075 or VTX-2337, have been found to very potently activate expression of multiple inflammatory genes (including interleukin 6 [IL6], tumor necrosis factor [TNF], CSF3, IL12B, IL23A, EBI3, and CCL23) and production of the corresponding products (Arruda-Silva et al, 2017;Cassatella et al, 2020;Tamassia et al, 2019;Zimmermann et al, 2015Zimmermann et al, , 2016) by human neutrophils. In particular, we found that the induction of IL6 gene transcription via TLR8 activation depends on active remodeling of chromatin at the IL6 genomic locus in human neutrophils, turning it from an ''inactive'' to an ''active'' configuration (Zimmermann et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…To date, TLR8 ligands, have been shown to trigger or modulate a variety of effector functions of neutrophils, including the survival, the respiratory burst, the phagocytic activities, and the formation of NETs (Thomas and Schroder, 2013). In our research, TLR8 agonists, including R848 and other compounds, such as CL075 or VTX-2337, have been found to very potently activate expression of multiple inflammatory genes (including interleukin 6 [IL6], tumor necrosis factor [TNF], CSF3, IL12B, IL23A, EBI3, and CCL23) and production of the corresponding products (Arruda-Silva et al, 2017;Cassatella et al, 2020;Tamassia et al, 2019;Zimmermann et al, 2015Zimmermann et al, , 2016) by human neutrophils. In particular, we found that the induction of IL6 gene transcription via TLR8 activation depends on active remodeling of chromatin at the IL6 genomic locus in human neutrophils, turning it from an ''inactive'' to an ''active'' configuration (Zimmermann et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…No expression of ISGs was observed in R848-treated neutrophils (as illustrated by Figures 1F and S1D) because they do not upregulate type I IFN expression (Zimmermann et al, 2015(Zimmermann et al, , 2016. Furthermore, cluster 7 was found to also include genes encoding for chemokines specifically expressed in monocytes, such as CCL7, CCL8, and CCL15, as well as immunoregulatory cytokines, such as IL7, IL15, IL10, and IL27 (Figure 1F), the latter two molecules already known as not transcribed in R848-stimulated neutrophils (Cassatella et al, 2020;Zimmermann et al, 2015). Finally, the genes included in clusters 8 and 9 were found to be related to ''response to molecule of bacterial origin'' GO terms (Figure S1C) and listed many of the cytokines recently shown to be produced by R848-stimulated neutrophils (e.g., IL6, CSF3, EBI3, IL12B, IL23A, CCL4, and CCL23) (Cassatella et al, 2020;Tamassia et al, 2019;Tamassia et al, 2018;Zimmermann et al, 2015) other than monocytes.…”
Section: Gene Expression Profiling In R848-stimulated Neutrophilsmentioning
confidence: 85%
See 2 more Smart Citations
“…While it was shown in the literature that overexpressed murine p19 can be secreted as a standalone protein, the human p19 subunit could only be detected in the conditioned medium if it was complexed with IL-23p40 [17]. However, recent papers underscore the possibility that the IL-23A-p19 subunit can be secreted as a standalone protein as shown that activated neutrophils and monocytes not only secrete the IL-23 p19/p40 heterodimer in cell supernatants, but also the IL-23A-p19 subunit which was not complexed with EBI3 [20]. In addition, a recent publication described that epthelial cancer cells could secrete the p19 subunit without being complexed to p40 beta subunit [21].…”
Section: Plos Onementioning
confidence: 99%